Penerapan Pemakaian Skin Wrap dalam Pengaturan Suhu Tubuh Bayi Baru Lahir di RS Awal Bros Grup - Indah Purnama Sari (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Newborns can experience hypothermia shortly after birth, hypothermia occurs through several mechanisms, which are related to the body's ability to balance heat production and heat loss. Failure caused by a decrease in the body temperature of the baby born falls by about 0.30C per minute. To avoid hypothermia, several ways can be done, including by using skin wrap. Skin wrap is a plastic bag to reduce heat loss due to evaporation so that it can easily increase the baby's temperature. The method of using skin wrap can be used to prevent hypothermia in neonates, both premature and not. Hypothermia in infants can worsen the condition of babies who lose heat after birth. Providing education and outreach regarding the application of skin wraps for newborns is carried out so that all nurses understand the importance of implementing this in order to maintain thermoregulation in newborns. Education was carried out for all nurses in the Awal Bros Group Hospital environment on May 25 2023 with a total of 94 participants which was carried out online with zoom.